Immuno-Modulatory Effects of Korean Mistletoe in MDA-MB-231 Breast Cancer Cells and THP-1 Macrophages - Wan-Taek Lim; Chang-Eui Hong; Su-Yun Lyu (MDPI AG, 2023)
Korean mistletoe (Viscum album var. coloratum) has been traditionally used as a remedy for cancer, diabetes, and hypertension. This study investigated the immuno-modulatory effects of Korean mistletoe water extract, specifically on MDA-MB-231 cells, a highly metastatic breast cancer cell line, when co-cultured with THP-1 human macrophage cells. When compared to MDA-MB-231 cells cultured alone, the co-culture of MDA-MB-231/THP-1 cells treated with mistletoe extract showed a significant reduction in IL-6 secretion. Additionally, these co-cultures exhibited elevated levels of IL-4, TGF-β, and IFN-y. These results suggest that water extracts from mistletoe have the potential to induce mitochondria-targeted apoptosis in MDA-MB 231 cells stimulated by THP macrophages. Regarding apoptosis, in MDA-MB-231 cells co-cultured with THP-1 macrophages, mistletoe water extract treatment triggered a significant increase in Bax/Bcl-2 ratio, caspase-3 activation, and PARP inactivation. In addition, there was a significant increase in E-cadherin and a decrease in N-cadherin. Treatment of Korean mistletoe also led to significant reductions in both MMP-2 and -9. Furthermore, inhibition of cell migration in MDA-MB-231/THP-1 co-cultured cells was observed. In summary, this study highlights the potential of Korean mistletoe as a prospective drug for the treatment of triple-negative breast cancer, particularly through its ability to regulate human immunity.